Utilization of Rituximab for Refractory Rowell Syndrome - Singh, Sukhraj; Sheffield, Sandra; Chowdhury, Nisha; Nuthulaganti, Swetha; Vaghaiwalla, Zareen; Ramsubeik, Karishma (Case Reports in Rheumatology, 2021)
Rowell syndrome describes the occurrence of erythema multiforme-like lesions in patients with cutaneous lesions of lupus erythematosus. The clinical picture of atypical erythema multiforme-like lesions, presence of chilblains, speckled ANA pattern, anti-Ro/SSA, or anti-La/SSB antibodies, and absence of infectious or pharmacologic triggers in a patient with systemic lupus erythematosus are some of the classic clinical and serologic features. Histopathologic and serologic findings can help differentiate this process from erythema multiforme. We present a case of young woman with systemic lupus erythematosus, end-stage renal disease due to lupus nephritis, and a remote history of Steven–Johnson syndrome due to sulfa allergy who presented to the hospital with a recurrent, progressive, targetoid erythematous rash involving more than 60% of her body surface area. Our patient had several hospitalizations in the recent past for this erythematous rash and had failed oral therapy with prednisone 1 mg/kg and hydroxychloroquine. In view of the minimal improvement and increasing severity and patient exhibiting early features of mast cell activation syndrome, the patient was treated with pulse intravenous glucocorticoids followed by rituximab with an excellent response. We highlight a unique case report of progressive Rowell syndrome refractory to standard of care with an excellent response to rituximab.